EMPLOYING AGENT-BASED SIMULATION TO UNDERSTAND THE BEHAVIOR OF DOMESTIC BEEF-CATTLE PRODUCTION - Andre R Daud; Utomo S Putro; Dhanan S Utomo (Universitas Padjadjaran, 2013)
The purpose of this paper is mainly to understand the behavior of domestic beef productionthrough estimating the dynamics of domestic cattle population. Agent based model (ABM) approachand its simulation is employed in this study. The main reason to use this approach is on its capabilityto accommodate the complexity given existing characteristics in cattle and beef production system.Based on the findings, agent-based model approach performs well in explaining the emergent behaviorfor agricultural production system, especially cattle production system. Several important implicationshave also been drawn from this study. Therefore, this study has generated several new insights that willbe advantages for further studies.